3(2x-7)=6+2(x-3)

Simple and best practice solution for 3(2x-7)=6+2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-7)=6+2(x-3) equation:


Simplifying
3(2x + -7) = 6 + 2(x + -3)

Reorder the terms:
3(-7 + 2x) = 6 + 2(x + -3)
(-7 * 3 + 2x * 3) = 6 + 2(x + -3)
(-21 + 6x) = 6 + 2(x + -3)

Reorder the terms:
-21 + 6x = 6 + 2(-3 + x)
-21 + 6x = 6 + (-3 * 2 + x * 2)
-21 + 6x = 6 + (-6 + 2x)

Combine like terms: 6 + -6 = 0
-21 + 6x = 0 + 2x
-21 + 6x = 2x

Solving
-21 + 6x = 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-21 + 6x + -2x = 2x + -2x

Combine like terms: 6x + -2x = 4x
-21 + 4x = 2x + -2x

Combine like terms: 2x + -2x = 0
-21 + 4x = 0

Add '21' to each side of the equation.
-21 + 21 + 4x = 0 + 21

Combine like terms: -21 + 21 = 0
0 + 4x = 0 + 21
4x = 0 + 21

Combine like terms: 0 + 21 = 21
4x = 21

Divide each side by '4'.
x = 5.25

Simplifying
x = 5.25

See similar equations:

| 30(20)(40)= | | -50=70 | | 2(8-a)/3=4-4a | | Z=25/(-3)(5) | | 4(x+6)=2(x-4) | | -4/7=5/6y | | 32-13+21=15 | | 3x=2x+30 | | 48(36)= | | 1/3h=-3 | | 5(2x+7)=-15 | | 25/(-3)(5) | | 2x+3y=276 | | p=q+3+s | | 100.00-36.49= | | 3x+2p=47 | | x-(-29)=27 | | 32-13+21=-31 | | 3(2-x)/5=x | | c(x+2)+-5=b(x+-3) | | 4x+8=2x+7 | | -1+45+23x=135 | | 5x^2+33x-55=0 | | -3+8x=2+8x-5 | | W=(-5/3-5)/(5/3+3) | | x-1/3x-1/2x=2 | | 1/2a=2 | | 13/78 | | 5(4w-20)=(5w-25) | | 16+6m=5(3m+5) | | (5/6)*(4/7) | | 1+2+y=5 |

Equations solver categories